2016
DOI: 10.1002/jhm.2572
|View full text |Cite
|
Sign up to set email alerts
|

Preparedness for hospital discharge and prediction of readmission

Abstract: Background, Objective Patients’ self-reported preparedness for discharge has been shown to predict readmission. It is unclear what differences exist in the predictive abilities of two available discharge preparedness measures. In order to address this gap, we conducted a comparison of these measures. Design, Setting, Patients Adults hospitalized for cardiovascular diagnoses were enrolled in a prospective cohort. Measurements Two patient-reported preparedness measures assessed during post-discharge calls: t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 15 publications
1
25
0
5
Order By: Relevance
“…Yet, very few studies have examined whether data collected prospectively from patients add to the predictive power of existing risk models for readmissions. Mixon and colleagues examined an 11-item measure that assesses how prepared patients feel when leaving the hospital (B-HOSPITAL) 31. They concluded that it did not add meaningfully to the LACE index when predicting 30-day readmissions for patients with cardiovascular diseases, but might still help to direct care transition quality improvement efforts.…”
Section: The Need To Engage More Systematically With Patientsmentioning
confidence: 99%
“…Yet, very few studies have examined whether data collected prospectively from patients add to the predictive power of existing risk models for readmissions. Mixon and colleagues examined an 11-item measure that assesses how prepared patients feel when leaving the hospital (B-HOSPITAL) 31. They concluded that it did not add meaningfully to the LACE index when predicting 30-day readmissions for patients with cardiovascular diseases, but might still help to direct care transition quality improvement efforts.…”
Section: The Need To Engage More Systematically With Patientsmentioning
confidence: 99%
“…Assessing patients' readiness for discharge is becoming increasingly important for ensuring their safety, satisfaction, and physical, emotional, and social outcomes (Weiss, Ryan, & Lokken, 2006;Weiss et al, 2007). Recent research has offered convincing evidence that discharge readiness is associated with readmission likelihood, and even mortality (Coffey & McCarthy, 2013;Mixon et al, 2016;Weiss et al, 2007). To ensure safe discharge, patients' readiness for discharge must be assessed accurately (Patel & Mourad, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Mixon and colleagues also recently reported that the CTM-3 score was not significantly associated with 30day or 3-month death/readmission in 1239 patients with cardiovascular diagnoses in Tennessee-the c-statistic for the CTM-3 score was only 0.52 for 30-day outcomes in their study. 21 While an examination of the Medicare Hospital Compare database reported statistically significant inverse relations between CTM-3 scores and 30-day readmission rates after hospitalizations for heart failure, pneumonia, or acute myocardial infarction, all of the correlations were weak (with correlation coefficients between − 0.20 and − 0.30). 22 We found that patients who received the HCAHPS survey differed from those who were not surveyed in several baseline factors-this was not surprising since AHS selected medical and surgical patients and excluded psychiatric patients and certain obstetric cases from the HCAHPS surveys.…”
Section: Discussionmentioning
confidence: 99%